The Evidence Behind the Diagnostic Investigation of Canine Idiopathic Epilepsy - Charalambous, Marios; Brodbelt, David; Volk, Holger Andreas (Veterinary Evidence, 2016)
Clinical bottom line There remains until recently an overall lack of clarity for the practical criteria for the diagnosis of canine idiopathic epilepsy. Signalment and an interictal neurological examination are vital for the diagnosis of idiopathic epilepsy. Despite the current insufficient evidence, the emerge of new diagnostic methods, such as cerebrospinal fluid and/or serum biomarkers, advanced functional neuroimaging techniques and electroencephalography, is likely to change the diagnostic approach in canine epilepsy in the near future.